188k views
5 votes
Drag each tile to the correct box. Not all tiles will be used.

Arrange the equations in the correct sequence to find the inverse of

Drag each tile to the correct box. Not all tiles will be used. Arrange the equations-example-1

2 Answers

2 votes

Inverse:

1) x = (y - 4) / (33 - y)

2) x(33 - y) = y - 4

3) 33x - xy = y - 4

4) 33x + 4 = y + xy

5) 33x + 4 = y (1 + x)

6) y = f^-1 = (33x + 4) / (1 + x)

User Heartless Vayne
by
4.6k points
2 votes

For this case we must list the steps to find the inverse of the following function:


y = \frac {(x-4)} {(33-x)}

We exchange variables:


x = \frac {(y-4)} {(33-y)}

We solve for "y":


x (33-y) = y-4\\33x-xy = y-4\\33x + 4 = y + xy

We factor y:


33x + 4 = y (1 + x)

We clear y:


y = \frac {33x + 4} {1 + x}\\f ^ {- 1} = \frac {33x + 4} {1 + x}

Answer:

The order is:

G, I, A, D, B, H

User Cocoahero
by
5.1k points